TECHNOLOGIES OF THE SOLUTION OF POLYMER COMPOSITIONS FOR THE MANUFACTURE OF FUEL PRODUCTS - SMACHYLO, OKSANA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The work is devoted to the characteristics of the technologies for obtaining a polymer composition for the manufacture of decorative products. Research is focused on the technology of manufacturing polymer composite material based on polyvinyl chloride for the production of rigid pipes, fittings, sidings, windows and doors, profiles, fences, railings, various devices, valves, housings of inspection lights, ventilation ducts, fans, heat exchange equipment, parts of chemical equipment , laboratory devices and other products. The paper describes the manufacturing technology of the PVC composition and investigates the important performance characteristics of the polymer melt. Three common technologies are presented, they are rolling, calendering and extrusion. The most common material for the manufacture of polymer. This composition is most often obtained by the extrusion method, so this section focuses on this technology in more detail resin products is a polyvinyl chloride composition. The stiffness of the polymer is characterized by the modulus of elasticity during bending. To determine this indicator, samples of polymer material without irradiation and with UV irradiation for a certain period of time were used. When the content of chalk in the recipe increases, the hardness increases. All compositions are characterized by approximately the same character - with exposure to six hours, the modulus of elasticity decreases, and with further exposure, it begins to gradually increase. The combination of а filler and a polymer is the most powerful for use in PVC compositions in the manufacture of decorative products.